Can somebody help me to prove this identity?

$$\prod_{k=1}^{n-1} \left(\;\cos\theta-\cos\frac{k\pi}{n}\;\right) = 2^{1-n}\sin(n\theta)\csc\theta$$

I was thinking of using the properties of the complex numbers and the binomial theorem, because I found this problem in the Complex Variables book from Schaum's, but it did not solve my problem.

Does anyone have an idea?

Thanks in advance!


Let $x=\sin(n\theta)\csc(\theta)$. I have to show that $x=2^{n-1}\prod_{k=1}^{n-1}(\cos(\theta)-\cos(k\pi/n))$.

Consider $t=e^{i\theta}=\cos\theta+i\sin\theta$. We have $(t-\bar t)\cdot x=(t^n-\bar t^n)$ and hence $$ \left(t^n-\frac{1}{t^n}\right)=\left(t-\frac{1}{t}\right)\cdot x. $$ Multiplying $t^n$ on both sides, we then have $t^{2n}-1=(t^2-1)t^{n-1}\cdot x$. On the other hand, $$ t^{2n}-1=\prod_{k=0}^{2n-1}(t-\xi^k)=(t^2-1)\prod_{1\le k\le 2n-1,~k\ne n}(t-\xi^k), $$ where $\xi$ is the $2n$-th roots of unity. Note that $\xi=\bar\xi^{-1}$ and $\xi^{n+l}=\bar\xi^{n-l}$ for $1\le l\le n-1$. Thus
$$ \prod_{1\le k\le 2n-1,~k\ne n}(t-\xi^k)=\prod_{k=1}^{n-1}(t-\xi^k)(t-\bar\xi^k)=\prod_{k=1}^{n-1}(t^2-(\xi^k+\bar\xi^k)t+1)\\ =t^{n-1}\prod_{k=1}^{n-1}\left(t-(\xi^k+\bar\xi^k)+\frac{1}{t}\right)=t^{n-1}\prod_{k=1}^{n-1}\left(t-(\xi^k+\bar\xi^k)+\bar t\right)\\ =t^{n-1}\cdot 2^{n-1}\prod_{k=1}^{n-1}\left(\cos(\theta)-\cos\left(\frac{k\pi}{n}\right)\right). $$ Hence the assertion $x=2^{n-1}\prod_{k=1}^{n-1}(\cos(\theta)-\cos(k\pi/n))$ follows.

  • 1
    $\begingroup$ $$ t^{2n}-1=\prod_{k=0}^{2n-1}(t-\xi^k) $$ is sort of obvious, but I had forgotten it and had to look it up. $\endgroup$ – Keith McClary Jan 7 '18 at 5:10

The Chebyshev polynomials of the second kind satisfy the relation $$U_n(\cos(\theta)) = \frac{\sin((n+1)\theta)}{\sin(\theta)}$$

Hence $U_{n-1}(\cos(\theta)) = \sin(n\theta)\csc(\theta)$.

Note that $\prod\limits_{k=1}^{n-1}(x-\cos(k\pi/n))$ is a polynomial of degree $n-1$ which has $n-1$ distinct zeros corresponding to $x = \cos(k\pi/n), k = 1, \ldots, n-1$.

But $U_{n-1}(\cos(k\pi/n))=\sin(k\pi)\csc(k\pi/n) = 0, k = 1, \ldots, n-1$.

Hence $U_{n-1}(x)$ is a polynomial of degree $n-1$ with the same zeros as the product above.

This means $\prod\limits_{k=1}^{n-1}(x-\cos(k\pi/n)) =CU_{n-1}(x)$ for some constant $C$ which must be determined.

The coefficient of $x^{n-1}$ in $U_{n-1}(x)$ is $2^{n-1}$ but it is $1$ in the product. Therefore $C = 2^{1-n}$.

Therefore $\prod\limits_{k=1}^{n-1}(x-\cos(k\pi/n)) = 2^{1-n}U_{n-1}(x)$ and after substituting $x$ and using the relation stated above, we find $$\prod\limits_{k=1}^{n-1}(\cos(\theta)-\cos(k\pi/n)) = 2^{1-n}U_{n-1}(\cos(\theta)) = 2^{1-n}\sin(n\theta)\csc(\theta)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.